1983
DOI: 10.1148/radiology.146.1.6294733
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomographic study of hormone-secreting microadenomas.

Abstract: A review was made of the computed tomographic (CT) studies of 33 patients with hormone-secreting microadenomas that had been verified by transsphenoidal surgery and endocrinologic evaluation. In previous studies in small series of patients, the CT appearance of pituitary microadenomas has been reported as hypodense, isodense, and hyperdense. In this study, CT showed a region of diminished enhancement and usually an enlarged pituitary gland in cases of prolactin-secreting adenomas. HGH- or ACTH-secreting adenom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
3

Year Published

1986
1986
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(10 citation statements)
references
References 0 publications
0
7
0
3
Order By: Relevance
“…Other reports in the literature also document a preponderance of small microadenomas in recent series of patients with Cushing's disease [5,6,16,17]. Information about the accuracy of CT scanning is scant, but in one series of 12 patients [4] the sensitivity was approximately 18% and the falsenegative rate was approximately 73% for microadenomas, while in a second series [6] the sensitivity was 22% in a group of nine microadenomas. Better sensitivity was found in a group [18] in which 12 of 19 patients with biochemical abnormalities suggestive of ACTH pituitary adenomas were found to have hypodense lesions on coronal CT.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Other reports in the literature also document a preponderance of small microadenomas in recent series of patients with Cushing's disease [5,6,16,17]. Information about the accuracy of CT scanning is scant, but in one series of 12 patients [4] the sensitivity was approximately 18% and the falsenegative rate was approximately 73% for microadenomas, while in a second series [6] the sensitivity was 22% in a group of nine microadenomas. Better sensitivity was found in a group [18] in which 12 of 19 patients with biochemical abnormalities suggestive of ACTH pituitary adenomas were found to have hypodense lesions on coronal CT.…”
Section: Discussionmentioning
confidence: 97%
“…In recent years, high-resolution CT of the sella turcica has almost completely replaced all other imaging techniques in the investigation of abnormalities of the pituitary gland. However, there is scant information about the diagnostic accuracy of this procedure, especially in regard to the identification of adenomas in Cushing's disease [1][2][3][4][5][6] . Over a period of 5 years between 1980 and 1985, 35 patients who had coronal CT scans of the sella turcica at the Montreal General Hospital for suspected ACTH-secreting adenoma underwent transsphenoidal ex ploration.…”
Section: The Diagnostic Accuracy Of Preoperative Ct Scanning In the Ementioning
confidence: 99%
“…The controversy has arisen from the varying frequency with which sellar or pituitary changes considered to be indicative of a prolactin secreting microadenoma have either been found in subjects without endocrine pathology (Muhr et al 1981;Swartz, Russell, Basile, ODon-nellandPopky 1983) or proved to be diagnostically incorrect at surgery (Raji, Kishore and Becker 1981;Davis, Hoffman, Tindall and Braun 1985). However, other studies have shown excellent correlation between radiological and surgical findings (Keye, Chang, Wilson and Jaffe 1980;Teasdale, Macpherson and Teasdale 1981;Hemminghytt, Kalkhoff, Daniels, Williams, Grogan and Haughton 1983;Kucharczyk et al 1986;Marcowitz et al 1988;Stadnik et al 1990).…”
Section: Discussionmentioning
confidence: 99%
“…On noncontrast scans, a microadenoma can be hypointense and isodense to the gland. 28,29 Similar to MR imaging, thin-section dynamic imaging is helpful for detection, particularly for the …”
Section: Evaluation Of the Sellar And Parasellar Regionsmentioning
confidence: 99%